Intrinsic UV-VUV luminescence and X-ray emission spectroscopy of BeO and multicomponent oxide dielectrics - Ivanov, V.; Pustovarov, V.; Kikas, A.; Kaambre, T.; Kuusik, I.; Kirm, M. (Functional Materials, 2012)
The experimental study of intrinsic UV-VUV luminescence and X-ray emission at the selective excitations near fundamental absorption edge as well as at the inner-shell excita-tions for binary BeO crystal and multicomponent oxide crystals Be₂SiO₄, Y₂SiO₅ and La₂Be₂O₅ has been performed. The results show that relaxation during the time-scale of decay of short-living anion and cation excitations leads to creation of self-trapped excitons at the same low-symmetry local structural units of crystalline lattice. The applied experimental method gives an opportunity to clarify a participation of different crystalline units of complex oxides in the self-trapping of excitons. Виконано експериментальне дослідження власної УФ-ВУФ люмінесценції і рентгенівської емісії для бінарного BeO і комплексних Be₂SiO₄, Y₂SiO₅ й La₂Be₂O₅ кристалів при селективному збудженні поблизу краю фундаментального поглинання і в області поглинання остовних рівнів. Результати дослідження показують, що релаксаційні процеси, що відбуваються протягом часу життя короткоживучих як аніонних, так і катіон-них збуджень приводять до утворення автолокалізованих екситонів у тих самих низьких-симетричних локальних структурних фрагментах кристалічної гратки. Використаний експериментальний метод дозволяє встановити ступінь участі різних фрагментів кристалічної гратки у процесах автолокалізації екситонів у комплексних оксидах. Выполнено экспериментальное исследование собственной УФ-ВУФ люминесценции и рентгеновской эмиссии для бинарного ВеО и комплексных Be₂SiO₄, Y₂SiO₅ и La₂Be₂O₅ кристаллов при селективном возбуждении вблизи края фундаментального поглощения и в области поглощения остовных уровней. Результаты исследования показывают, что релаксационные процессы, происходящие в течение времени жизни короткоживущих как анионных, так и катионных возбуждений приводят к образованию автолокализованных экситонов в одних и тех же низко-симметричных локальных структурных фрагментах кристаллической решетки. Использованный экспериментальный метод позволяет установить степень участия различных фрагментов кристаллической решетки в процессах автолокализации экситонов в комплексных оксидах.